Immersive ParaView: An Immersive Scientific Workflow for the Advancement of Measurement Science - Su, Simon; Lopez-Coto, Israel; Sherman, William R.; Sayrafian, Kamran; Terrill, Judith (IEEE International Symposium on Mixed and Augmented Reality Workshops (Online), 2022)
We present ongoing work to enhance ParaView with new immersive visualization capabilities and demonstrate its use in the development of our scientific workflow in support of visual analytics in an immersive environment to advance measurement science. Two case-studies of complex meteorology and radio-frequency (RF) data as part of the knowledge discovery process reveal the benefits of interactively exploring the three-dimensional data with immersive technologies such as the CAVE and head mounted display virtual reality. By adding support of immersive technology into Para View, researchers can more naturally investigate the data of three-dimensional simulations. These efforts to provide tools for immersive visualization are guided by the need to advance measurement science, standards, and technology. To make these tools more broadly accessible and impact-ful, we promote the use of software standards related to visualization and immersive systems.